Understanding International Immobility through Internal Migration: “Left behind” Nurses in the Philippines - Ortiga, Yasmin Y.; Macabasag, Romeo Luis A. (The International migration review, 2021)
Migration scholars have tended to portray internal mobility as a step toward broader cross-border movement, reinforcing the notion of ongoing progress toward international migration. This article argues for a need to recognize how internal mobility can also explain international immobility, or why people do not move across national borders. Using the case of Filipino nurses, we argue that while internal migration does allow aspiring migrants to build the potential ability to emigrate, individual trajectories are much more diverse and multi-directional, often prolonging or reinforcing their international immobility. As a result, and in our case study, the costs and burdens of constant internal movement can also alter nurses’ migration aspirations, prompting them to either alter their original goals or acquiesce to their inability to leave their origin countries. This article calls for migration scholarship to address not only a “mobility bias” within the field but also the over-focus on international migration, rather than internal mobility, as a subject of study.